Predicting hemorrhagic transformation and its timing from maximum cerebral lesion diameter in nonlacunar ischemic strokes. Issue 1 (17th December 2019) - Muscari, Antonio; Faccioli, Luca; Lega, Maria Vittoria; Lorusso, Andrea; Masetti, Marco; Pastore Trossello, Marco; Puddu, Giovanni M.; Spinardi, Luca; Zoli, Marco
Abstract: Objectives: We performed this retrospective cohort study to establish which factors are mostly indicative of the appearance of hemorrhagic transformation (HT) and of its time course in a sample of nonlacunar ischemic strokes. Materials and Methods: In 402 patients with nonlacunar ischemic stroke (75.0 ± 12.7 years, 192 male), clinical, laboratory, and neuroimaging variables obtained during the first 3 days of hospitalization were compared between patients with and without HT at computer tomography scan. Results: HT was documented in 129 patients (32.1%), including 36 with parenchymal hematoma (PH), after a median time of 6 days (range 1–27). Many variables were univariately associated with HT, but only 5 of them were confirmed in Cox regression (Hazard Ratio, 95% Confidence Interval): maximum cerebral lesion diameter (CLD) in cm (1.12, 1.06–1.18; p = .0001), hemoglobin in g/dl (1.16, 1.06–1.27; p = .002), blood glucose in mmol/L (1.10, 1.03–1.18; p = .007), prior anticoagulant therapy (1.82, 1.10–3.03; p = .02), and edema with mass effect (1.72, 1.08–2.75; p = .02). Thus, the most significant predictor was CLD. The overall risk of HT was minimum for CLD < 2 cm (1.5%), intermediate for CLD ≥ 2 and < 5 cm (22%), and maximum for CLD ≥ 5 cm (58%). The residual probability of having HT decreased progressively over time, and a simple formula is proposed to predict, from CLD in cm, when the probability of HT falls below 10%. Conclusions: The main determinant of HT was CLD, a simple quantitative parameter that could prove useful, in particular, in deciding the timing of anticoagulation in cardioembolic stroke patients. Abstract : In our sample of 402 nonlacunar ischemic strokes, the main predictors of hemorrhagic transformation were as follows: (a) cerebral lesion diameter, (b) blood glucose, (c) prior anticoagulant therapy, (d) cerebral edema with mass effect, (e) hemoglobin concentration. A simple relationship between cerebral lesion diameter and the timing of hemorrhagic transformation has been found, which could be considered in deciding when starting anticoagulation after a cardioembolic stroke.